Total synthesis of diospyrol an anthelmintic drug from diospyros mollis griff - C. Mahidol (2018)
Diospyrol 4 is constructed from a masked butadiene synthon, anthracene adduct 1 [R = H]. The key construction steps comprise tandem Michael addition-Dieckmann condensations, first between anion 7 and 1, and subsequently between anion 7 and 15. © 1989.